Pengaruh Edukasi Kesehatan Terhadap Kesiapsiagaan Masyarakat Dalam Pertolongan Pertama Hipoglikemia Di Kecamatan Belawang - Sri Purwanti Ariani; Indrayadi .; Yuhansyah .; Ernawati .; Rapika . (CV. ITTC INDONESIA, 2026)
Hypoglycemia is an emergency condition that frequently occurs in individuals with Diabetes Mellitus and may lead to decreased consciousness and life-threatening complications if not managed promptly and appropriately. In Belawang District, high population density, limited access to healthcare services, and low health literacy have resulted in inadequate community preparedness to provide first aid for hypoglycemic events. Despite strong social potential, such as active community health volunteers and a culture of mutual cooperation, the community’s ability to recognize symptoms and deliver initial assistance remains limited. This activity aims to improve community knowledge and skills in recognizing the signs of hypoglycemia and providing timely, appropriate, and safe first aid through simulation-based emergency training. The program is expected to strengthen community preparedness and self-reliance in managing daily emergencies, particularly hypoglycemia. Furthermore, this activity supports the achievement of Sustainable Development Goal (SDG) 3 on good health and well-being and contributes to strengthening the role of higher education institutions in community service.